THE INFLUENCE OF COMPENSATION, CAREER DEVELOPMENT, AND ORGANIZATIONAL CULTURE ON EMPLOYEE RETENTION - Wachid Hasym; Permana Permana; Rustianah Rustianah (Utan Kayu Publishing, 2024)
In the era of globalization and increasingly fierce business competition, companies are faced with the challenge of retaining qualified employees. Competent and experienced employees are valuable assets for organizations because they contribute significantly to the achievement of company goals. Therefore, employee retention is an important strategic issue to be considered by company management. Compensation is one of the main factors that influence employees' decision to stay with a company. According to several studies, fair and competitive compensation can increase employee satisfaction, which in turn has a positive impact on employee retention. Good compensation includes not only basic salary, but also incentives, bonuses, allowances, and other facilities that can improve employee welfare. Thus, effective compensation management is crucial in the effort to retain employees. Career development is another very important aspect in influencing employee retention. Employees tend to feel more satisfied and committed to companies that provide clear and structured career development opportunities. Training programs, further education, mentoring, and transparent career paths can help employees feel valued and motivated to continue growing within the organization. Research shows that employees who see career development prospects where they work tend to have higher loyalty to the company. A strong and positive organizational culture also plays an important role in employee retention. A culture that is supportive, inclusive and in line with employees' personal values can increase their sense of attachment to the company. Organizational culture includes values, norms, and behaviors that are accepted and shared by all members of the organization. When employees feel that the organizational culture matches their personal values, they tend to be more at home and motivated to stay with the company. The objectives of this study are: to find out whether compensation, career development and organizational culture affect employee retention both partially and simultaneously. Then the stages in this research methodology are to test the validity and reliability of the research instrument, after passing these tests, the classical assumption test will then be carried out and then use multiple linear regression tests where the data will be processed using minitab statistical software / SPSS. The implication of this research is that the company will later find out what variables can affect employee retention, especially in the variables of compensation, career development, and organizational culture.